2011
DOI: 10.1038/nature09681
|View full text |Cite
|
Sign up to set email alerts
|

A massive protocluster of galaxies at a redshift of z ≈ 5.3

Abstract: Spitzer IRAC fluxes were measured from a combination of programs 20070 (COSMOS) , 40801, 50310 and 61043 (SEDS) in the COSMOS field. The data for program 61043 were obtained during the Spitzer warm mission and only the data obtained in January 2010 were used for this paper. The average exposure time at the position of the proto-cluster is 6.3 hours per pixel.The data reduction procedure closely follows that used for the COSMOS data (program 20070) 29 . We began our reduction using the corrected basic calib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
378
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(403 citation statements)
references
References 39 publications
24
378
1
Order By: Relevance
“…Several protoclusters have been found at z > 2 with overdensities of galaxies extending tens of Mpc across e.g. (Venemans et al 2007;Carilli et al 2011;Casey et al 2015;Capak et al 2011). …”
Section: Ulasj1234+0907: a Significant Overdensity Of Millimetre Brigmentioning
confidence: 99%
“…Several protoclusters have been found at z > 2 with overdensities of galaxies extending tens of Mpc across e.g. (Venemans et al 2007;Carilli et al 2011;Casey et al 2015;Capak et al 2011). …”
Section: Ulasj1234+0907: a Significant Overdensity Of Millimetre Brigmentioning
confidence: 99%
“…Thus the DSFGs seen in GN20 are likely the galaxies that will evolve in to brightest cluster galaxies (BCGs). Capak et al (2011) examined the COSMOS data set, and found four galaxies at z ∼ 5.3, all centered around an extreme starburst originally detected with the AzTEC camera at 1.1 mm, COSMOS AzTEC-3 (Younger et al, 2007). The system has an inferred star formation rate of ∼ 1500 M yr −1 , and within 2 Mpc of the starburst, there are 11 objects with luminosities greater than L * .…”
Section: Environments Of Dsfgsmentioning
confidence: 99%
“…Scott et al, 2008;Aretxaga et al, 2011) and has been responsible for the discovery of some of the highest redshift SMGs known around z ≈ 5 (e.g. Capak et al, 2011).…”
Section: Aztec 2005-presentmentioning
confidence: 99%
“…(See, for example, Falder et al [2011] and Capak et al [2011], who find two galaxies in the z ¼ 5:3 cluster bright enough to be detected by SERVS at 4.5 μm.) For comparison, the largest structures seen in the Millennium simulation at z ∼ 1 are of the order of 100 Mpc (Springel et al 2005), which subtends 3°at that redshift, so each SERVS field samples a wide range of environments.…”
Section: Introductionmentioning
confidence: 99%